Features of the Organization of Pedagogical Practice - Abdullayev, Sukhrob Sayfullayevich; Hamroyev, Jamshid Bafoyevich (European Journal of Life Safety and Stability (2660-9630), 2021)
This Article Is Written About The Organization Of Pedagogical Practice And Also Given Recommendations, Goals And Objectives For Students - Practice Students Of The Iv Bachelor Of Fine Arts And Engineering Graduation.